Introductory experiments on biomolecules and their interactions - Delong, Robert K.; Zhou, Qiongqiong (London : Academic Press, 2015)
Introductory Experiments on Biomolecules and their Interactions provides a novel approach to teaching biomolecules in the lab. While featuring the requisite fundamentals, it also captures the author's experience in industry, thus providing unique, up-to-date experiments which take the learning experience one-step further. The text parallels lectures using a standard biochemistry undergraduate text. Unlike most current lab manuals available in the market which simply emphasize an introduction of techniques, this lab manual provides students with opportunities to demonstrate and prove the knowledge and theories they learn from class.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed March 18, 2015).
Elsevier
Keywords: Biomolecules -- Laboratory manuals; Molecular biology -- Laboratory manuals; Biomolecules; Molecular biology; Electronic books; Laboratory manuals